Implementasi Surat Edaran No. 15 Tahun 2020 Tentang Pedoman Penyelenggaraan Belajar dari Rumah dalam Masa Darurat Penyebaran Corona Virus Disease (Covid-19) bagi Guru SD Negeri Kabupaten Pemalang - Putri Cintya Cipi; Suyitno Suyitno; Intan Rahmawati (STKIP Andi Matappa Pangkep, 2021)
Circular No. 15 of 2020 issued by the Ministry of Education and Culture regarding the process of learning from home. The purpose of this study was to determine the extent to which the implementation of distance learning was carried out by elementary school teachers in Pemalang Regency with the Circular of the Minister of Education and Culture No. 15 of 2020. This type of research is descriptive qualitative research with a naturalistic approach. The data collection technique used a questionnaire (questionnaire). The data sources used are answers to questionnaires that have been filled out by 86 public elementary school teachers in Pemalang district. The results of this questionnaire analysis indicate that the teacher has implemented Circular No. 15 of 2020 concerning Guidelines for Organizing Learning From Home in an Emergency Period for the Spread of Corona Virus Disease (Covid-19). With the acquisition of 70%-90% the answers agree and strongly agree on each statement stating that the implementation of home learning is based on the Circular of the Ministry of Education and Culture No. 15 Year 2020.